The Impact of Occupational Stress on Employee Performance in Maldives Tourism Industry (International Journal of Scientific Research and Management (IJSRM), 2023)
This study was conducted to investigate the relationship between occupational stress on employee performance in the Maldives tourism industry. Descriptive research design was adopted for primary data collection. A questionnaire containing 24 items with Likert 5-point scale (1: strongly disagree – 5: strongly agree) was developed as the research instrument to collect quantitative data. The questionnaire was divided into three parts: the first part sought demographic characteristics; the second part sought responses on causes of stress (work overload, inadequate compensation, career concerns and interpersonal conflicts) as independent variables; The dependent variable was employee performance and part three of the questionnaire comprises factors to identify the impact of stress on the dependent variable. A total of 270 respondents were selected from various tourist resorts in the Maldives by employing convenience sampling technique. Regression techniques using SPSS26 were carried out to analyze and evaluate the impact of occupational stress on employee performance. The findings of the study showed that both work overload and inadequate compensation have significant negative impact on employee performance. The other two independent variables, career concerns and interpersonal conflicts found to have no significant impact on employee performance. Hence, it was concluded that increased workload and inadequate compensation escalates level of stress and significantly reduces employee performance. Therefore, it is recommended for managers not to increase employees’ work demands in a way that exceeds the individual’s ability to complete the assigned tasks. It is also imperative for managers to ensure that the employees’ benefit package or compensation reflects the amount of effort they invest on work. This will help to reduce the level of stress and enhance employees’ performance. Since there are limited/no past researches in the context of Maldives tourism industry, future research should be more structured and consider exploring different variables that contribute to stress and are not used in this research. This will help to draw a better understanding of the subject and would also facilitate to obtain an improved analytical result.